Study of base-catalyzed aldol reaction of trimethylsilyl enolates - Sutar, R. L.; Joshi, Navalkishore N. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Mukaiyama-type aldol reaction of trimethylsilyl enolates with aldehydes in the presence of a base is a complicated reaction. It usually results in various products determined by the nature of base and reaction medium. The present study has been undertaken to understand these factors and design new Lewis base catalysts to optimize the yield of desired aldol product. It has been shown that mild Bronsted base with inbuilt hydrogen bonding sites are efficient catalysts for the reactions involving trimethylsilyl enolates. Based on the observed results, a mechanism is proposed to explain the reaction outcome.
Keywords: Aldol reaction; base catalyzed; carboxylate salts; lithium amides